Understanding and Perceptions of Women of Reproductive Age towards Breast Self-Examination as an Effort for Early Detection of Breast Cancer - Arlina, Andi (Advances in Healthcare Research, 2024)
Purpose: This study aims to analyze in depth the understanding and perceptions of women of childbearing age regarding breast self-examination (BSE) as an early detection measure for breast cancer. The primary focus is on technical knowledge, subjective meaning, and social and cultural influences that shape women's health behaviors. Research Design and Methodology: This study employs a qualitative approach, grounded in a Systematic Literature Review (SLR). The articles analyzed were selected based on their relevance to the theme, the time frame of 2015–2024, and publication in reputable international journals such as SAGE, BMC, and Elsevier. The analysis process involved extracting thematic data from various sources to identify patterns, gaps, and determinants of behavior related to SADARI. Findings and Discussion: The findings indicate that although most women of reproductive age are aware of SADARI, a significant gap remains between knowledge and practice. Factors such as shame, fear, social stigma, and cultural norms significantly influence the shaping of attitudes and behaviors. In addition, internal factors such as motivation and self-efficacy also influence the decision to perform SADARI regularly. Implications: This study highlights the importance of a contextual and responsive educational approach to addressing the social realities faced by women of reproductive age. The findings can serve as a basis for designing community interventions and culturally informed health policies to increase participation in breast cancer early detection practices.